Evidence for abnormal visuospatial attentional processes in the interictal migraineur. Issue 5 (2nd September 2020) - Kriegler, Conley; Cruz, Maria T.; Sun, Gloria; Friedrich, Trista E.; Elias, Lorin J.; Mickleborough, Marla J. S.
ABSTRACT: Research shows decreased brain region activity in the right temporo-parietal junction (rTPJ) in people with migraine headache relative to headache-free controls when performing an orienting visuospatial attention task. Functional inactivation of the rTPJ has been associated with rightward performance deviations on laterality-based attention Landmark (LM) and greyscale (GRE) tasks in individuals with unilateral neglect and heightened activation in the rTPJ is associated with leftward deviation, known as pseudoneglect, in controls on these tasks. Given this, we investigated whether migraineurs would lack the leftward deviation found in headache-free controls on visuospatial attention tasks. 36 migraineurs and 38 controls were presented with LM and GRE tasks. Response bias scores showed a significant difference in responses between groups ( p = 0.036) on the GRE, a luminance-based task, but not on the LM, a size-based task ( p = 0.826). This study is the first to show laterality-based attentional differences in migraineurs, as compared to controls. Specifically, migraineurs were found to have smaller leftward biases on luminance-based visuospatial attention tasks, as compared to controls, aligning with previous research suggesting that migraine may be having an impact on a variety of attention tasks in migraineurs in between headache attacks.